2004
DOI: 10.1080/00016480310002122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological study of vertigo at an outpatient clinic

Abstract: A correct diagnosis is essential to ensure adequate treatment and attain an acceptable balance between cost and effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 6 publications
6
40
1
3
Order By: Relevance
“…[3][4][5][6][7] In the present study, as well as in previous studies, dizziness/vertigo was more common for women than for men in all age groups. 7,[9][10][11][12][13][14]29 However, women also have higher rates of sickness absence in general, 19,30,31 often explained by occupational differences. 19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] In the present study, as well as in previous studies, dizziness/vertigo was more common for women than for men in all age groups. 7,[9][10][11][12][13][14]29 However, women also have higher rates of sickness absence in general, 19,30,31 often explained by occupational differences. 19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…3,8 Dizziness/vertigo is a common symptom, increasing with age, 7 and the frequency is higher in women than men. 7,[9][10][11][12][13][14][15] Lifetime prevalence was estimated to be 30% in a German survey, 11 while a study from Scotland reported 21% vertigo, 29% unsteadiness, and 13% other types of dizziness. 10 In a sample of general practices in London, 24% reported patients with dizziness in the last month.…”
Section: Introductionmentioning
confidence: 99%
“…11 Vertigo becomes more prevalent with increasing age and the reported frequency is higher in women. [12][13][14][15] The subjective nature of vertigo demands clinicians to follow a multidimensional approach to management including attention to detailed history, vestibular assessment using otolaryngological diagnostics, and treatment algorithms. 3 With a fluctuating episodic pattern of symptoms, vertigo treatment aims to minimize or eliminate the number and severity of acute attacks, reduce tinnitus, and prevent impaired vestibular functions.…”
Section: Introductionmentioning
confidence: 99%
“…At clinic presentation, other symptoms may be necessary in making the diagnosis of the aetiology [2]. For example, cochlear symptoms like tinnitus and hearing loss may suggest that the pathology is in the labyrinthine or VIII cranial nerve [3]. Symptoms like diplopia, dysarthria and facial weakness may suggest brain stem causes.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms like diplopia, dysarthria and facial weakness may suggest brain stem causes. Drug history, duration, co-morbidities and previous surgeries are also very important in making the diagnosis [3]. In Benign Paroxysmal Positional Vertigo, there is usually a latent phase and the vertigo only last for a few seconds (5-10secs), in the migraine type, it usually can last from some minutes to a few hours.…”
Section: Introductionmentioning
confidence: 99%